Human resource management practices recruitment, training & benefits: a study on Radisson Blu Dhaka Water Garden Hotel - Hossain, Tamman (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.